2020
DOI: 10.1155/2020/4878315
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Blood and Body Fluids among Medical Laboratory Science Students of the University of Health and Allied Sciences during Vocational Internship in the Volta Region of Ghana

Abstract: Medical laboratory science students (MLSS), likewise health care workers (HCW), invariably get exposed to blood and body fluids (BBF) of patients. The degree of exposure of these students is even worsened due to their inexperience, which is usually revealed during their vocational training programme. This study therefore determined the prevalence of exposure to BBF and its risk factors among MLSS at the University of Health and Allied Sciences (UHAS). A cross-sectional survey was employed using simple random s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… 35–40 Besides, needlestick injury prevalence over the 12-month duration ranged from 14.0% in a study done in the Volta Region to 66.0% in a study conducted in the Northern Region. 35 37 40–42 A lifetime prevalence of needlestick injuries was reported as 54.6% in a study conducted in the Northern Region. 41 Further, two studies conducted in the Volta and Greater Accra Regions reported a 12-month prevalence of splash of blood and body fluids at 21.3% and 60.5%, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“… 35–40 Besides, needlestick injury prevalence over the 12-month duration ranged from 14.0% in a study done in the Volta Region to 66.0% in a study conducted in the Northern Region. 35 37 40–42 A lifetime prevalence of needlestick injuries was reported as 54.6% in a study conducted in the Northern Region. 41 Further, two studies conducted in the Volta and Greater Accra Regions reported a 12-month prevalence of splash of blood and body fluids at 21.3% and 60.5%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of sharp instrument-related injuries over 1 year ranged from 7.9% in a study conducted in the Volta Region to 53.7% in a study carried out in the Greater Accra Region 35–40. Besides, needlestick injury prevalence over the 12-month duration ranged from 14.0% in a study done in the Volta Region to 66.0% in a study conducted in the Northern Region 35 37 40–42. A lifetime prevalence of needlestick injuries was reported as 54.6% in a study conducted in the Northern Region 41.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Prevalence rates of 60.3%, 88.6%, 9.4%, 13.9% and 49% were found in China, Egypt, The United States, Australia and Turkey respectively. 9 , 10 To our knowledge, in Morocco, no study has been published to describe the frequency of OBEA among nursing students. It is within this framework that the objective of this study falls, which aims to determine the prevalence and the factors associated with occupational exposure to biological material potentially infected by blood in a nursing student population.…”
Section: Introductionmentioning
confidence: 99%